2017
DOI: 10.1038/s41598-017-10106-6
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Origin of Short Tail in Endangered Korean Dog, DongGyeongi

Abstract: The tail of many animal species is responsible for various physiological functions. The functional importance of tail may have brought tail-loss to attention in many evolutionary and developmental studies. To provide a better explanation for the loss of tail, the current study aims to identify the evolutionary history and putative causal variants for the short tail in DongGyeongi (DG), an endangered dog breed, which is also the only dog in Korea that possesses a short tail. Whole genome sequencing was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 34 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…This finding challenges the notion that a genetic investigation is complete after a single diagnosis is obtained (Boycott & Innes, ). It is however noteworthy that in the traditional Korean DongGyeongi dog, the characteristic tail loss has been imputed to selective sweep genes including ANKRD11 (Yoo et al, ), thus indeed suggesting a role of this gene in coccyx development. Accordingly, KBG syndrome has to be considered in the differential diagnosis of patients with an elongated and prominent coccyx.…”
Section: Discussionmentioning
confidence: 99%
“…This finding challenges the notion that a genetic investigation is complete after a single diagnosis is obtained (Boycott & Innes, ). It is however noteworthy that in the traditional Korean DongGyeongi dog, the characteristic tail loss has been imputed to selective sweep genes including ANKRD11 (Yoo et al, ), thus indeed suggesting a role of this gene in coccyx development. Accordingly, KBG syndrome has to be considered in the differential diagnosis of patients with an elongated and prominent coccyx.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, seven local landrace populations, defined as distinct dog varieties unique to a specific geographic region with historically limited breeding populations, are included in this study. The latter are not recognized by any purebred canine registry but, nonetheless, may display a genetic pattern consistent with other purebreeds (Alam, Han, Lee, Ha, & Kim, 2012;Puja et al, 2005;Tanabe, 2007;Wijnrocx, Francois, Stinckens, Janssens, & Buys, 2016; Yoo et al, 2017), such as has been observed for one Italian regional population, the Fonni's Dog Dreger, Rimbault, et al, 2016;Sechi et al, 2016). By focusing our analyses on breeds with diverse phenotypes that have all originated in a single country, we aim to employ genetic data to expand upon historical breed formation accounts and define the modes by which humans have produced recognizable and diversified dog breeds.…”
mentioning
confidence: 99%
“…The genome sequencing data of Donggyeong dogs with different tail lengths [long tail, N = 7 (~20 coccygeal bones); short tail, N = 5 (5~7 coccygeal bones); non-tail, N = 10 (2~3 coccygeal bones)] was obtained from a recent study 16 . The genome sequencing data of additional 12 dog breeds [Diqing village dog, German shepherd, Kunming dog, Lijiang village dog, Tibetan mastiff, and Yingjiang village dog (N = 10 for each breed), Indian village dog (N = 3), Lebanon village dog (N = 1), modern European breed (N = 1), Nambia village dog (N = 1), Portugal village dog (N = 2), and Vietnam village dog (N = 2)], which was used in another recent study 19 , was downloaded from the NCBI SRA database ( http://ncbi.nlm.nih.gov/sra ; SRA accession numbers are in Supplementary Table 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…To preserve unique features of Donggyeong dog, studies have been performed by cloning 15 . Recently, whole-genome sequencing data of 22 Donggyeong dogs was generated, and their unique genetic structure and the development of short tail phenotype were investigated 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation